Good Governance in the Dynamics of Recruitment of Polri Members Year 2015-2019 - Setyadi, Rakhmad; Rahayu, Rahayu; Yuwono, Teguh; Dwimawanti, Ida Hayu (Budapest International Research and Critics University, 2021)
The phenomenon that occurs in the recruitment process for members of the Indonesian National Police in realizing Good Governance is following the principles of good management, such as Clean, Transparent, Accountable, and Humanist. This is intended so that the philosophy of the right man on the right place remains the basis for consideration in the context of recruiting members of the National Police. However, it is possible to accept the recruitment of members of the National Police, which is considered to be full of acts of corruption, collusion and nepotism (KKN). The purpose of this study is to analyze the problems faced by Polri in managing the principles of good governance through the BETAH principle in the recruitment of Polri members in 2015-2019. The research method used in this study is a descriptive method with a qualitative approach that is oriented towards naturalistic or natural phenomena, aiming to understand human and social problems. The results of the study show that various irregularities still occur in the recruitment and selection process for the National Police organized by Polda throughout Indonesia. The various modes of deviation include: (1) fraud and embezzlement by promising to pass, (2) the policy of prioritizing local sons, (3) leaking test questions, and (4) abuse of authority. These various problems occur because there are still gaps that have the potential for irregularities in the mechanism of the National Police recruitment and selection process, so this study will also discuss issues related to the mechanism of the National Police recruitment and selection process which still has the potential for such irregularities to occur. The selection of the National Police, which is held by all regional committees in all regional police units, must be able to formulate regulations and mechanisms that can ensure the implementation of the National Police recruitment and selection process based on a merit system.